Optimal sites for miniscrew insertion in anterior aesthetic region: a CBCT study for different vertical skeletal patterns - Xiaoyan Feng; Luxi Weng; Xin Li; Yiyang Shen; Jun Lin (BMC Oral Health)
Abstract Introduction The objective of this retrospective cohort study was to measure the root distance, bone thickness and bone density in maxillary anterior region with different vertical skeletal patterns based on CBCT data, and provide reference for the optimal site for miniscrew insertion in anterior aesthetic region. Methods 60 adult patients(18-29years) with skeletal Class I angle (ANB angle = 2° ± 2°) were selected and divided into three groups (n = 20) according to vertical skeletal patterns.The population was divided into 3 groups according to the measured SN-GoGn angle: hypodivergent (SN-GoGn < 27°), average (27°≤ SN-GoGn ≤ 37°) and hyperdivergent (SN-GoGn > 37°) groups. The CBCT data was processed and measured by Dolphin Imaging and Mimics Medical. Measurement indicators included interradicular distances (IRD), overall bone thickness (OBT), cortical bone thickness (CBT), cortical and cancellous bone density (CoBD & CaBD). One-way ANOVA test of variance was used for statistical comparisons. Results IRD increased with apical height, reaching an maximum average measurement of 4.750 ± 1.226 mm at 10 mm axial section. Within the same axial section, the IRD of the region between the two central incisors was significantly larger than that of the other regions. There was no statistical difference in IRD among different vertical skeletal patterns. OBT increased with vertical height in the 2–6 mm axial sections, and no significant difference among three groups. There was a statistical difference of the CBT at 4–8 mm axial sections among the three groups (P < 0.05), but not at 10 mm axial section. There was no statistical difference (P < 0.05) of CaBD among different vertical skeletal patterns. However, there are statistically difference of CoBD in many regions between hypodivergent and hyperdivergent groups. Conclusions The anatomical structure in anterior aesthetic region of individuals varies greatly, and interradicular distances is not affected by vertical skeletal pattern. However, in general, hypodivergent patients have higher bone density and greater bone thickness than that of hyperdivergent patients, which means more safe regions to choose for miniscrew insertion.